2023
DOI: 10.1128/mbio.00769-23
|View full text |Cite
|
Sign up to set email alerts
|

LaeA-Regulated Fungal Traits Mediate Bacterial Community Assembly

Abstract: Cheese rinds are economically important microbial communities where fungi can impact food quality and aesthetics. The specific mechanisms by which fungi can regulate bacterial community assembly in cheeses, other fermented foods, and microbiomes in general are largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In this study, it was found that genes for fumagillin and pseurotin were physically intertwined in a single supercluster. Pseurotin is not described as having a role in aspergillosis, but interestingly, this metabolite has been recently found to exhibit antibacterial properties and mediate the bacterial composition of the cheese rind microbiome [60].…”
Section: Timeline Of Linkage Of Natural Products To Specific Bgcsmentioning
confidence: 99%
“…In this study, it was found that genes for fumagillin and pseurotin were physically intertwined in a single supercluster. Pseurotin is not described as having a role in aspergillosis, but interestingly, this metabolite has been recently found to exhibit antibacterial properties and mediate the bacterial composition of the cheese rind microbiome [60].…”
Section: Timeline Of Linkage Of Natural Products To Specific Bgcsmentioning
confidence: 99%
“…Gene‐editing tools have become more widely available, allowing researchers to test evolutionary hypotheses in a much wider range of organisms (e.g. Karageorgi et al., 2019; Tannous et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…If a cluster‐specific transcription factor is encoded inside the cluster, this is the first gene to be expressed and in turn activates all other cluster genes. In addition, global regulators like LaeA are required for the coordinated expression of the genes (Keller et al., 2006; Tannous et al., 2023). Applying these parameters to whole‐genome transcriptomic approaches helps to identify novel gene clusters.…”
Section: Biosynthesis—from Simple To Complexmentioning
confidence: 99%